Effect of livestock on the growth of Rosa rubiginosa in a mountain range: A dendrochronological approach - Mestre, Luciana Mariel (2014)
In the present study, we used dendrochronological tools to determine the effect of domestic livestock on the cumulative radial growth of Rosa rubiginosa, a shrub native to Europe that has been introduced to the mountains of central Argentina. We described R. rubiginosa growth rings, we built a ring width chronology using 18 stems from a homogeneous site, and finally compared rings width in 40 individuals distributed in areas with and without livestock but otherwise similar. Our results demonstrated the negative effect of livestock on the cumulative radial growth of invasive species R. rubiginosa. In this sense, the livestock would be acting as a biotic filter for the invasion of this species in the mountains of Córdoba (Argentina) and may be considered as a tool to reduce R. rubiginosa growth in invaded areas, where livestock will not cause other damages. We consider that the measurement of annual ring width against datable basal stems represents a simple method for the determination of radial growth rates. This approach could be particularly useful for monitoring the effects of land management practices on the invasion of woody species. © 2014, ALÖKI Kft., Budapest, Hungary.